Multi-Response Optimization of 1 Kg Mass Artifact and Gravimetry as A Control Process in Legal Metrology Mass Laboratories Using the Taguchi Method and Response Surface Methodology - Saufik Luthfianto; Sandi Satria; Irfan Santosa (The Indonesian Institute of Science and Technology Research, 2026)
Artifacts are instruments used as reference standards or objects agreed upon at the national level. The reference standard must have a degree of accuracy based on measurements conducted by competent personnel. Another standard involves laboratory support facilities, including proper temperature, humidity, and lighting conditions. The purpose of applying standards is to minimize measurement errors and uncertainties. Therefore, standards in Legal Metrology ensure that all measuring instruments are traceable in terms of accuracy, both nationally and internationally. However, if the intercomparison results of a region fall outside the upper and lower limits in terms of artifact output, it is considered a failure, requiring room temperature standardization based on the optimal value of artifact actualization. The research method used is the Taguchi method combined with response surface methodology. This method is one of the mathematical approaches to quality control and is applied from the earliest stage, namely the design phase. The orthogonal array used is L8(24). The response measured is the actualization of a 1-kilogram special accuracy class weight artifact and gravimetry. The controlled and varied independent variables include AC temperature, actualization duration, lighting intensity, and the number of operators in the laboratory. Currently, the optimization process of laboratory conditions is still performed manually by laboratory operators, making it difficult to control the independent variables. Therefore, this study will implement the Internet of Things (IoT) to assist operators in setting independent variables for laboratory conditions. The research results show that the optimal conditions include an AC temperature of 16°C, an actualization duration of 15 minutes, 50% lighting intensity, and 1 operator in the laboratory.